Modular finite element generators - Dy, Lorenzo
This thesis considers the generation of four finite element stifnesses and their corresponding generalized forces. It develops a series of common modules which may have different uses in different contexts. The generation of each element stiffness or generalized forces is done by assembling the appropriate modules or subroutines. The stiffness generated are given for the following elements: 1. in-plane triangular element 2. in-plane skew element 3. In-plane rectangular element 4.Plate bending rectangular element. Each element is accompanied by a numerical example and the results compared with conventional method. All modules or subroutines are coded in FORTRAN IV language. Computations were done in the IBM 360 Model 40 at the Computer Center of the University of the Philippines.